External costs of electric vehicles. (January 2016) - Jochem, Patrick; Doll, Claus; Fichtner, Wolf
Highlights: We provide a deep insight into external costs of electric vehicles. We differentiate between fuel type, vehicle size, emission location and time. External costs of electric vehicles are compared with those of conventional cars. We consider uncertainties of cost estimates. We show that electric vehicles (only) have a little advantage in external costs. Abstract: Electric vehicles (EV) are often considered a promising technology to decrease external costs of road transport. Therefore, main external cost components are estimated for EV and internal combustion engine vehicles (ICEV). These include costs of accidents, air pollution, climate change, noise, and congestion. All components are estimated over the product lifetime and, where appropriate, differentiated according to fuel type, vehicle size as well as emission location and time. The advantage of this differentiation is, however, compensated by high uncertainties of most cost estimates. Overall, the external costs of EV and ICEV do not differ significantly. Only for climate change, local air pollutants in congested inner-cities, and noise some advantageous effects can be observed for EV. The advantages depend strongly on the national electricity power plant portfolio and potentially also on the charging strategy. Controlled charging might allow for higher emission reductions than uncontrolled charging of EV.